Does Knowledge Sharing Mediate the Relationship between Training and Development on Employee Performance? Case of Food and Beverages Industry - Nur Constance, Wah; Lee Ru, Lai; Azuriaty, Atang (i-CATS Research Management Centre, 2025)
The food and beverage industry in Sarawak is dynamic with strong growth prospects driven by local culture, tourism, and a robust agriculture based. The rise of urbanisation and the growth of middle to upper class has contributed to the market potential. Recognising the importance of employee performance in this food and beverages industry, the study seeks to investigate in what way knowledge sharing mediates the relationship between training and development and employee performance. Using social exchange theory as the underpinning theory, seven hypotheses were tested. The study utilised quantitative methods and through statistical analysis, the study examines the direct and indirect effects of training and development on employees performance while examining the mediating effect of knowledge sharing. The results suggested that effective training, development and fostering learning culture should be implemented within the food and beverage industry. This study provides improvement in employee performance and contributes to overall business success in the food and beverage industry. Keywords: Training, Development, Employee Performance, Knowledge Sharing, Social Exchange Theory.